PENGEMBANGAN MULTIMEDIA BERBASIS ARTICULATE STORYLINE 3 MENGGUNAKAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VI SD TENTANG PENYESUAIAN MAKHLUK HIDUP DENGAN LINGKUNGANNYA - Damayanti, Islamia Diana; Sri Handono, Sri Handono Budi Prastowo; Ketut, A. A. Ketut Budiastra (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
The development of multimedia based on Articulate Storyline 3 with the Contextual Teaching and Learning (CTL) approach aims to improve the learning outcomes of grade VI elementary school students in understanding the concept of adaptation of living things to their environment. Contextual learning through interactive multimedia is designed to attract students' interest and relate learning materials to their daily lives. The methodology of this study uses the Research and Development (R&D) approach with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model to develop and test the effectiveness of the multimedia product. The test results show that the use of CTL-based multimedia provides a significant increase in learning outcomes in the experimental group. Compared to the control group, with an N-Gain score of 95.41% for the experimental group which is in the very effective category. The discussion shows that the CTL approach is able to increase the relevance of learning and motivate students to be active, while the interactive features of Articulate Storyline 3 support conceptual understanding through more concrete visualization. This study confirms that the combination of CTL and interactive multimedia can be an innovative solution in improving the quality of science learning in elementary schools. The implication is that the application of technology in contextual-based education can overcome the constraints of traditional learning and increase students' absorption of scientific concepts. Keywords: Articulate Storyline 3; Contextual Teaching and Learning (CTL); Learning Outcomes